Exponentiated Generalized Transformed-Transformer Family of Distributions - Nasiru, Suleman; Mwita, Peter N.; Ngesa, Oscar (Scienpress Ltd, 2017)
Recently, the development of generalized class of distributions has become an issue of interest, to both applied and theoretical statisticians, due to their wider application in different fields of studies. Thus, the current work proposed a new generalized family of distributions called the exponentiated generalized transformed-transformer family. Some members of the new family such as the exponentiated generalized half logistic family was discussed. Statistical measures such as quantile, moment, moment generating function and Shannon entropy for this new class of distributions have been derived.
Keywords: Exponentiated generalized T-X; Quantile; Shannon entropy